Parameters of effective competition activity and selection of young gymnasts in age 9-10 years - Bolyak, A. A.; Pomazan, A. A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to determine the effective factors of competitive activities and criteria for selection of young gymnasts at the stage of preliminary basic training based on the tests of motor skills and physiological parameters using methods of statistical analysis.